NBCe2 (Slc4a5) Is Expressed in the Renal Connecting Tubules and Cortical Collecting Ducts and Mediates Base Extrusion - Barbuskaite, Dagne; Pedersen, Fredrik D.; Christensen, Henriette L.; Johnsen, Laura Ø.; Praetorius, Jeppe; Damkier, Helle H. (Frontiers in Physiology, 2020)
Arterial hypertension, is a common disorder with multiple and variable etiologies. Single nucleotide polymorphism analyses have detected an association between variants in the gene encoding the electrogenic Na+:HCO3– cotransporter NBCe2 (Slc4a5), and salt-sensitive hypertension. Mice with genetic deletion of NBCe2 are hypertensive, and the cause of the blood pressure (BP) increase is believed to arise from a lack of renal NBCe2 function. The exact cellular expression of NBCe2 in the kidney tubular system is, however, not determined. Here, we find NBCe2 to be expressed predominantly in isolated connecting tubules (CNT) and cortical collecting ducts (CD) by RT-PCR. In isolated renal CNT and CCD, genetic deletion of NBCe2 leads to decreased net base extrusion. To determine the role of renal NBCe2 in the development of hypertension, we generated CNT and intercalated cell NBCe2 knockout mice by crossing an Slc4a5 lox mouse with mice expressing cre recombinase under the V-ATPase B1 subunit promotor. Although the mice displayed changes in the expression of renal membrane transporters, we did not detect hypertension in these mice by tail cuff recordings. In conclusion, while global NBCe2 deletion certainly causes hypertension this study cannot confirm the role of renal NBCe2 expression in blood pressure regulation.